Drawing the Mind: Breaking the Discourse on Mental Health - Mariën, Maico (FRAME, Journal of Literary Studies, 2026)
This article problematizes the discursive ways mental disorders are perceived through a close reading of Joshua W. Cotter’s comic Driven by Lemons, which is a diary Cotter kept shortly after his diagnosis with bipolar II. The way he depicts this journey draws out, what Jean-François Lyotard termed the “figure,” which emphasizes destruction over structure. By using Jason Helms’s method of oscillating between looking at and through, this paper highlights the ways Driven by Lemons reveals the figure and, in this way, is able to disrupt dominant discourses. Thus, it highlights the important ways comics can draw out nuances of mental disorders and challenge the main discourse in place.